The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1177/107110070602701220
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Mechanical Properties of Calcaneal Artificial Specimens, Fresh Frozen Specimens, and Embalmed Specimens in Experimental Testing

Abstract: Artificial calcanei (Sawbone, Synbone) showed different biomechanical characteristics than cadaver bones (embalmed and fresh-frozen) in this experimental setup with biocompatible cyclic loading. These results do not support the use of artificial calcanei for biomechanical implant testing. Fresh-frozen and embalmed specimens seem to be equally adequate for mechanical testing. The low variation of mechanical strength in the unpaired cadaver specimens suggests that the use of PAIRED specimens is not necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…The different unpaired human cadaveric femur bones were harvested from different donors; thus, we could not compare the different fixation techniques on a paired bone model. Zech et al (2006) found a low degree of variation in mechanical strength in similar unpaired cadaveric bone specimens. For a better comparison of the specimens, we chose a similar group of donors concerning sex and age distribution.…”
Section: Discussionmentioning
confidence: 84%
“…The different unpaired human cadaveric femur bones were harvested from different donors; thus, we could not compare the different fixation techniques on a paired bone model. Zech et al (2006) found a low degree of variation in mechanical strength in similar unpaired cadaveric bone specimens. For a better comparison of the specimens, we chose a similar group of donors concerning sex and age distribution.…”
Section: Discussionmentioning
confidence: 84%
“…Our study was performed on formalin fixed bone, due to better availability. Some authors found it equal to the quality of fresh frozen bone [22]. On the other hand animal studies have revealed disadvantages [17,21].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the destructive nature of mechanical testing (most specimens tested to failure), the order of such testing is traditionally reserved for the latter stages of most studies, where specimens have undergone other non-destructive analyses prior to mechanical testing. Tissue fixation with 10% formalin (4% formaldehyde) is widely used to preserve specimens without refrigeration, offering researchers the added benefit of protection from specimens with communicable diseases (Boskey et al, 1982;Nimni et al, 1987;Wilke et al, 1996;Nuccion et al, 2001;Moreno and Forriol, 2002;Randall et al, 2002;Wingerter et al, 2006;Zech et al, 2006). However, researchers refrain from using formalin to decontaminate and preserve bone tissue to be tested mechanically, since its effects on the mechanical properties of bone have been the subject of much debate.…”
Section: Introductionmentioning
confidence: 97%